Design of Automatic Garden Watering Based on Solar Cell - Aldi Satria Budi (Brilliance: Research of Artificial Intelligence, 2022)
In this study, an automatic garden watering device was designed using a solar cell composed of semiconductors that function to convert sunlight into electric power directly. The additional equipment used is a timer, BCU, rain sensor, relay, and inverter. The purpose of the design and design of this tool is to determine the performance of the automatic garden watering design by utilizing solar cells as a voltage source, as well as to find out how the control system works by incorporating rain sensors when watering plants optimally so that it can be utilized by the community. . As for the test results when the solla cel without using a load, the resulting voltage is 15 volts, the resulting current is 1.5 amperes. When a load is used, the resulting voltage decreases to 11.5 volts, the current increases to 5.73 amperes. The output voltage and current with the inverter are 214 volts and 1.05 amperes, respectively. When measurements were made, the voltage and current produced by the battery were 11.8 volts and current 7.8 amperes, respectively, while the voltage increased and current decreased in the inverter were 221 volts and 0.81 amperes, respectively.